CLEAR: The Morphological Evolution of Galaxies in the Green Valley - Vicente Estrada-Carpenter; Casey Papovich; Ivelina Momcheva; Gabriel Brammer; Raymond C. Simons; Nikko J. Cleri; Mauro Giavalisco; Jasleen Matharu; Jonathan R. Trump; Benjamin Weiner; Zhiyuan Ji (The Astrophysical Journal, 2023)
Quiescent galaxies having more compact morphologies than star-forming galaxies has been a consistent result in the field of galaxy evolution. What is not clear is at what point this divergence happens, i.e., when do quiescent galaxies become compact, and how big of a role does the progenitor effect play in this result? Here we aim to model the morphological and star formation histories of high-redshift (0.8 < z < 1.65) massive galaxies ( $log(M/M_{\odot })$ > 10.2) with stellar population fits using Hubble Space Telescope/WFC3 G102 and G141 grism spectra plus photometry from the CANDELS Ly α Emission at Reionization (CLEAR) survey, constraining the star formation histories for a sample of ∼400 massive galaxies using flexible star formation histories. We develop a novel approach to classifying galaxies by their star formation activity in a way that highlights the green valley population, by modeling the specific star formation rate distributions as a function of redshift and deriving the probability that a galaxy is quiescent ( P _Q ). Using P _Q and our flexible star formation histories we outline the evolutionary paths of our galaxies in relation to stellar mass, Sérsic index, effective radius R _eff , and stellar mass surface density. We find that the galaxies show no appreciable stellar mass growth after entering the green valley (a net decrease of 4%) while their stellar mass surface densities increase by ∼0.25 dex. Therefore galaxies are becoming compact during the green valley and this is due to an increase in the Sérsic index and a decrease in R _eff .